Analysis of Language Errors at the Semantic Level in Political News in the Pekanbaru Tribun Newspaper - Pebri Ayuni; Alber (UIR Press, 2022)
Political news is an event concerning constitutional issues and is related to government. Political news covers the life of the bang and the country which has an impact on the lives of the people. In the political news of Tribun Pekanbaru, there is a language error semantic level. The problem in this research is how wrong it is language at the semantic level in the political news of the Pekanbaru Tribun newspaper ? The purpose of this research is to describe, analyze, interpret, and summarizes the language errors at the semantic level in political news Tribun Pekanbaru newspaper. The method in this research is the Content method Analysis (Content Analysis). Sources of data in this study are newspapers Tribun Pekanbaru edition 1 s.d. 30 September 2020. The approach used in this research is a qualitative approach. This type of research is library (library research). The results of data management were found In this study, namely: (1) Errors due to the c0-parents Tribun Pekanbaru found 3 data, (2) Errors due to the confounding partner contained in the news Political newspaper Tribun Pekanbaru found 5 data, (3) errors because of the wrong choice of words found in newspaper political news The Pekanbaru Tribune found 24 data. From the above explanation, it is an error because the choice of words that are not correct is found more than mistake because the couple was confused